Implementasi Algoritme Grain V1 Dan 128 Bit Pada Raspberry PI - Syahifudin Shahid; Ari Kusyanti; Rakhmadhany Primananda (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
NIST (National Institute of Standard Technology) is the institution that regulates data security standards. NIST held a project called eSTREAM to update old outdated stream ciphers. The grain algorithm is selected as a security algorithm on the hardware side and replaces the previous stream cipher. Grain algorithm has 2 versions, 80 bit and 128 bit. Security at the hardware level is also required to keep information data. With the update of security standards from NIST, this research is conveying the idea to utilize the grain algorithm for data security that will be implemented in raspberry pi. This study chose raspberry pi due to the large use of this mini PC in the Internet of Things and there is no update data stream cipher security. Raspberry pi that has been implemented with grain will do 3 testing that is test of keystream validation with test vector, time of execution process of IV and Key to produce keystream and encryption and data decryption. The test of execution time, will be analyzed using Independent t test test, the result of testing of keystream execution time on grain v1 and 128 algorithm is -2,146 with probability (Sig.) 0,000 indicates a significant difference, as well as with execution time of 8, 12 and 16 bit encryption and decryption. This research concluded raspberry pi performance for both stable versions.